Alive inside - Rossato-Bennett, Michael; Cohen, Dan (Social worker); Sacks, Oliver, 1933-2015; McFerrin, Bobby; Projector Media (Firm); Soundview Media Partners ([New York, N.Y.] : Projector Media, 2014)
A joyous cinematic exploration of music's capacity to reawaken our souls and uncover the deepest parts of our humanity. Filmmaker Michael Rossato-Bennett chronicles the astonishing experiences of individuals around the country who have been revitalized through the simple experience of listening to music.
Originally produced in the United States as a motion picture in 2014
Dan Cohen, William Thomas, Connie Tomaino, Oliver Sacks, Bobby McFerrin, Ann Wyatt, Peter Whitehouse, Samite Mulando, G. Allen Powers, Greogry Petsko, Naomi Feil, Connie Kantor, Lucile Hanscom, Petr Janata, Becky Kurtz, Kathy Greenlee, Peter Davies.
Cinematographer, Shachar Langlev ; editors, Michael Rossato-Bennett, Mark Demolar, Manuel Tsingaris, David Zieff ; original score, Itaal Shur.
In English.
Winner of the Special Award, at the Boston Film Festival 2014
Winner of the Audience Award, at the Sundance Film Festival 2014
Keywords: Music therapy; Alzheimer's disease -- Alternative treatment; Alzheimer's disease -- Patients -- United States; Dementia -- Alternative treatment; Dementia -- Patients; Documentary films; Nonfiction films; Feature films; Internet videos; Streaming video